THE ASSORTMENT STRUCTURE AND THE PRICE LEVELS AS A FACTOR OF MARKETING CHANNEL COMPETITIVENESS–EMPIRICAL EVIDENCE FROM THE REPUBLIC OF SERBIA - Jelena Končar; Sonja Leković; Goran Vukmirović (Ekonomski Vjesnik, 2016)
In this paper, the authors point out the differences in the structure of the product assortment of retailers who show their offers on the Web, with the aim of proving that the structure of the assortment may be a factor of marketing channel competitiveness that the consumers recognize and that makes them opt for a certain marketing channel. On the same basis we aim to compare the prices of representative product categories, in order to determine the impact of prices on marketing channel competitiveness, without taking other factors of channel competitiveness into consideration. Based on the conducted research, we can conclude that having a number of categories of products in the assortment presents a competitive advantage for the retailer in the traditional marketing channel since retailers with electronic sales have a more diverse assortment in their retail store than online. Compared to “pure play” electronic retailers, the structure of assortment measured in number of categories of products that are on offer in e-stores is not significantly different between “pure play” and “bricks and clicks” electronic retailers. On the other hand, if we look at the price levels, there is a difference in prices of product categories on websites of “brick and click” retailers since prices in retail stores are higher than prices in the traditional retail store of the same retailer. However, offers on the website of “pure play” electronic retailers are higher compared to “brick and click” retailers.